Analisis Tematik Hadis tentang Kerjasama Modal dalam Perspektif Syariah - Hafid, Abd.; Kara, Aisyah; Ahmad, Arifuddin (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research aims to analyze capital cooperation as discussed in several Hadith collections. Therefore, it employs the maudhui (thematic) method to examine various Hadiths concerning capital cooperation found across different Hadith compilations. This examination delves into the ontological, epistemological, and axiological aspects of Hadiths on capital cooperation, specifically how they manifest social worship in economic activities as a form of social responsibility. The findings indicate that there are approximately 50 Hadiths related to capital cooperation that use the term